Artificial Intelligence: Implications for English Language Teaching - Abdul-Malik Saif Thabet Al-Selwi (WISE Pendidikan Indonesia, 2025)
Artificial intelligence (AI) has made significant changes in several fields. It covers many applications and is still a rather multidisciplinary and emerging field. English Language Teaching (ELT), which is a branch of applied linguistics, is one of those fields that has received a huge impact from advanced AI empowerment technologies and applications, such as chatbots and tutoring systems. This study, therefore, examines the impact of AI on ELT, and the various ways that AI influences ELT. It explores the new future roles of teachers and learners in English classrooms, which will be AI-driven. The study is qualitative in nature, which explores emerging trends and themes in AI and ELT and examines potential developments. Through qualitative analysis of recent scholarly publications, the research identified key and emerging techniques for integrating AI in ELT classrooms. It employed thematic analysis to examine the data collected, focusing on experts' perspectives regarding future opportunities, trends, and prospects in AI and ELT. AI technologies and applications provide innovative techniques that cater to each 21st century learner’s needs, autonomy, and engagement with different proficiency levels, and give effective feedback to English teachers. They also foster language acquisition, can help identify the strengths and weaknesses of learners, and offer English teachers opportunities to customize lessons and enhance their teaching strategies. All these make the English learning process operative, more appealing, and tailored. This paper, therefore, provides valuable implications and insights for practitioners, learners, applied linguists, and higher educational institutions in developing relevant teaching materials and training programs for teachers.